2022
DOI: 10.1177/14705958221120343
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the mediating effect of Islamic Work Ethic (IWE) on the relationship between job satisfaction and job performance in Arab work environment

Abstract: Studying the role of religion and its relationship to work outcomes is not new in cross-culture management, especially in globalization with the increase of interaction in cross-cultural settings. Islamic work ethics (IWE) have attracted the attention of academics studying the attitudes and behaviors of workers in Muslim societies. This study investigates the role of IWE as a mediator in the relationship between job satisfaction and performance. A stratified sampling technique was used to select 11 emergency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Conversely, a declining Islamic work ethic results in poorer employee performance. This is supported by previous research by (AL Smadi et al, 2023), Udin et al (2022), andMohammed et al (2018) which stated that Islamic work ethic has a significant effect on employee performance. The results showed that individuals with a high level of Islamic work ethic were more likely to work hard to achieve their departmental goals and go beyond the demands of their basic jobs to help organizations and colleagues.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, a declining Islamic work ethic results in poorer employee performance. This is supported by previous research by (AL Smadi et al, 2023), Udin et al (2022), andMohammed et al (2018) which stated that Islamic work ethic has a significant effect on employee performance. The results showed that individuals with a high level of Islamic work ethic were more likely to work hard to achieve their departmental goals and go beyond the demands of their basic jobs to help organizations and colleagues.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research (AL Smadi, Amaran, Abugabah, & Alqudah, 2023) The results of previous research conducted by Maudi (Hijriatin, M., Arwiyah, M. Y., Fakhri, M., & Luturlean, 2021) state that work productivity directly influences employee performance, leading to the achievement of company goals. Meeting work targets within a set period is a key aspect of assessing employee performance, aimed at continuous improvement and positive impact on the company.…”
Section: Introductionmentioning
confidence: 99%